The real-world outcomes of vedolizumab in patients with ulcerative colitis in Korea: a multicenter retrospective study. (July 2021) - Ye, Byong Duk; Cheon, Jae Hee; Song, Ki Hwan; Kim, Joo Sung; Kim, Young-Ho; Yoon, Hyuk; Lee, Kang-Moon; Kang, Sang-Bum; Jang, Byung Ik; Park, Jae Jun; Kim, Tae Oh; Lee, Dae-Wook; et al.
Aim: This study examined the real-world effectiveness and safety outcomes of vedolizumab in ulcerative colitis (UC) patients who had failed anti-tumor necrosis factor (anti-TNF) therapy in Korea. Methods: A retrospective chart review study was conducted in adults with moderate to severely active UC who had failed anti-TNF agents and subsequently received vedolizumab. Clinical response and clinical remission at week 6 and 14 after vedolizumab initiation was evaluated. Safety outcomes were also reported. Outcome rates were compared with a matched sub-cohort derived from the open-label sub-cohort of the GEMINI 1 trial using the optimal matching method. Results: A total of 105 patients (mean age, 45.3 years; 63.8% male) were included. At week 6, 55.8% ( n = 43/77) achieved a clinical response and 18.2% ( n = 14/77) achieved clinical remission. At week 14, 73.2% ( n = 52/71) achieved a clinical response and 39.4% ( n = 28/71) achieved clinical remission. When non-response imputation was used, the clinical response rate at week 6 and week 14 were 40.1% ( n = 43/105) and 49.5% ( n = 52/105) respectively. Of the 105 patients, 16 (15.2%) experienced at least one adverse event. The matched analysis showed that the clinical response rate at week 6 was higher in the matched sub-cohort of this study (24/47, 51.1%) versus the matched sub-cohort from the GEMINI 1 open-label cohort (12/47, 34.3%, p = 0.019). The clinical remission rates at week 6 were similar (7/47, 14.9% versus 9/47, 19.1%, p = 0.785). Conclusions: In the real-world setting, vedolizumab is effective and well tolerated within the first 14 weeks of use in Korea. The proportion of patients experiencing clinical response and clinical remission at 6 and 14 weeks appeared to be largely consistent with that observed in real-world studies from other regions and populations.